Analisis Hermeneutika Maskot Osi dan Ji - Paku Kusuma; Dharsono Dharsono; Martinus Dwi Marianto; Guntur Guntur (Institut Seni Indonesia Denpasar, 2022)
Osi and Ji are city mascots that were inaugurated at the end of 2016 by the city government of Malang in conjunction with the celebration of its 103rd anniversary. The mascots which are resulted from a contest were made by Papang Jakfar and won through several stage stages process including presentation from hundreds of participants. This brings its own fascination as the use of mascots as city icons has not been so popular in Indonesia due to the complex composition of its creation process, from its relationship with the culture, resources, community characteristic to infrastructure facilities of a city. This complexity is summed up in the form of a city mascot as a paradox. Form in hermeneutics is text and can be viewed polisemically, so interpretation becomes a central problem. Thus, hermeneutics aims to verstehen (comprehend) through the method of abduction, not just interpreting. Interpretation is always a reconstruction of the meaning of a text. Analysis with hermeneutics method becomes an immanent part in the mascot's profanity as a design product, mascot's form is an entity created from the results of thinking in design that is loaded with consideration and ability of a qualified individual. Osi and Ji mascots are specifically analyzed by applying Paul Ricouer's theory of Hermeneutics, in which hermeneutics can be brieflydefined as a theory or philosophy of interpretation of meaning that analyzes the various symbols in its form. The objective of the research is to analyze more deeply and interpret the existing circumstances or relationships, ongoing processes, ongoing effects or emerging phenomena, since the results of the Osi and Ji analysis generate to a new knowledge formed from various entities.